Unmet Physical and Mental Healthcare Needs Among Stimulant-using Gay and Bisexual Homeless Men. (2nd September 2015) - Salem, Benissa E.; Nyamathi, ANP, Adey; Reback, Cathy; Shoptaw, Steven; Zhang, Sheldon; Nudelman, Olga
Abstract : The aim of this study was to gain a greater understanding of predictors of the unmet physical and mental healthcare needs of homeless, stimulant-using, gay and bisexual (G/B) men. This study correlated baseline self-reported unmet physical and mental healthcare needs among stimulant-using homeless G/B men ( n = 422, 18–46 years of age). A structured questionnaire was administered at baseline and data were collected from October 2009 to January 2013. The study was approved by the University of California Human Subjects' Protection committee and the Friends Research Institute Human Research Protection Committee. Logistic regression revealed that those who self-reported ever being married, being in fair or poor health and in moderate-to-very severe pain, were more likely to experience unmet needs for physical health care. In terms of unmet mental health needs, those who self-reported moderate-to-very severe pain and/or those reporting having sex while high, were more likely to report unmet needs for mental health care. In contrast, those reporting receiving social support from others were less likely to have an unmet mental healthcare need. Research implications are discussed as they relate to access to healthcare needs among this vulnerable population.